IMPLEMENTASI PROGRAM PENINGKATAN PERAN PEREMPUAN MENUJU KELUARGA SEHAT SEJAHTERA (P3KSS) STUDI DI KELURAHAN SUMBER AGUNG KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Faradipa, Faradipa; Tresiana, Novita; Puspawati, Ani Agus (Jurnal Administrative Reform, 2024)
To achieve family prosperity, women play an important role in the process. Increasing family welfare will contribute to the country's efforts to reduce poverty levels, especially in areas with a relatively high concentration of poor people. In other words, one of the secrets of getting out of poverty and backwardness is women's active participation. Women must participate and be involved in all stages of development, along with the development of the P3KSS program to become one of the government's initiatives to strengthen the role of women in development. This research uses qualitative techniques combined with descriptive strategies. In this research, interviews, observation and documentation are the methods used to collect data. The study findings show that the standard indicators and targets are well defined; policy resources have not been fully utilized due to lack of funding; communication between organizations and related activities has not run smoothly in implementing the P3KSS program; the characteristics of implementing agents have been well received; the implementer's disposition to accept the program well; and optimal economic, social and political conditions and no political interests being exploited.